Speech text of international conference on natural products (ICNP) 2023 / Prof. Datuk Ts. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
It is with great pleasure and utmost honour that I address you all today as Vice-Chancellor to officiate the prestigious International Conference on Natural Products (ICNP) 2023. I extend a warm welcome to all esteemed guests and participants gathered here at the Aloft Hotel in Kuala Lumpur.